2018
DOI: 10.2147/copd.s172240
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroids for chronic obstructive pulmonary disease: what is their role in therapy?

Abstract: Inhaled corticosteroids (ICSs) are a mainstay of COPD treatment for patients with a history of exacerbations. Initial studies evaluating their use as monotherapy failed to show an effect on rate of pulmonary function decline in COPD, despite improvements in symptoms and reductions in exacerbations. Subsequently, ICS use in combination with long-acting β2-agonists (LABAs) was shown to provide improved reductions in exacerbations, lung function, and health status. ICS-LABA combination therapy is currently recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 90 publications
(179 reference statements)
1
59
0
5
Order By: Relevance
“…There are several clinical trials and meta-analyses that suggest a superiority of LABA/ICS combinations to respective monotherapies regarding exacerbation rates, lung function decline, and health status in COPD [2]. Our data might explain this superiority by an increased anti-inflammatory efficacy of the ICS through the reversion of the corticosteroid resistance by LABAs.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…There are several clinical trials and meta-analyses that suggest a superiority of LABA/ICS combinations to respective monotherapies regarding exacerbation rates, lung function decline, and health status in COPD [2]. Our data might explain this superiority by an increased anti-inflammatory efficacy of the ICS through the reversion of the corticosteroid resistance by LABAs.…”
Section: Discussionmentioning
confidence: 55%
“…COPD therapy is complicated by the partial resistance/insensitivity of the airway inflammation to inhaled corticosteroids (ICS) [1]. ICS use increases the risk of pneumonia in COPD [2]. Therefore, a careful assessment of ICS use in COPD is required, e.g., by identifying responder phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…regimen and dose) and study design-related factors (e.g. patient characteristics and definitions used) [41]. In the present study, the pneumonia risk for single-inhaler triple therapy ranged from no reported increase to a significant increase.…”
Section: Discussionmentioning
confidence: 57%
“…2. Evidence of higher risk of pneumonia and potential fragility fractures while on ICS [18][19][20]; and 3. The availability of safer, effective alternatives such as a combination inhaler for both long acting muscarinic antagonist (LAMA) and long acting beta agonist (LABA) [21].…”
Section: Introductionmentioning
confidence: 99%